Improving Indonesian Language Learning Outcomes on Understanding Feelings Material Through Differentiated Learning Models with the Help of Visual Media for Grade 2 Students at UPTD SDN 192 Barru - Ningsih, Andi Nurul Elvira; T, Nur Khalis; Wahyuddin, Wahyuddin (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This journal reviews the material on recognizing feelings through differentiated learning models for students in grade 2 of UPTD SDN 192 Barru. This study aims to determine the understanding of the material on recognizing feelings using differentiated learning models assisted by visual media in the Indonesian language learning process in grade 2 of UPTD SDN 192 Barru. This type of research is classroom action research (PTK). The research instrument is student worksheets (LKPD). The research data sources are the results of observations in class, interviews with homeroom teachers, and students. The results of the study showed that the increase in learning outcomes on the material on recognizing feelings using differentiated learning models assisted by visual media got good and quite satisfactory results. So it is in accordance with what the teacher expects. In cycle I, only 3 students completed and 10 students did not complete, while in cycle II all students achieved a completeness score of 13 students. Overall, student learning outcomes on the material on recognizing feelings increased at each meeting. The implementation process uses a differentiated learning model assisted by visual media that contains effective learning concepts on the material on recognizing feelings in Indonesian language learning. The impact of this material on recognizing feelings provides a deeper understanding and can understand the content of this material in a more enjoyable, inspiring and meaningful way.